ANALISIS PERSEDIAAN BAHAN BAKU MIE SAGU DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI, PROVINSI RIAU - Halimatus Sa'diah; Liswar Hamid; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was performed on 21 UMKM noodles sago in District High Cliff Meranti Islands District Riau Province. This study aims to determine the factors that lead to non-fulfillment of the realization of the raw materials sago noodles and raw material inventory systems Analyzing sago noodles in terms of the economic order quantity and safety stock. In this study the types and sources of data used in this study are primary and secondary data. Primary data is directly gather from respondents that related to the research object in 21 UMKM. Secondary data were obtained from government agencies that Disperindag and Forestry and Plantation Meranti Islands District. Data analysis method used is descriptive method of analysis using the EOQ (economic order quantity) and safety stock (safety stock). The results of this study indicate that the factors that lead to unfulfilled realization sago noodle raw material is a source of raw materials and raw material prices. Application of the method of EOQ (economic order quantity) is not appropriate when applied to 21 UMKM noodles sago. menggigat several things: (1) raw material price of corn starch is not always constant. (2) The cost of ordering and storage costs that exist in UMKM. (3) The raw material of corn starch is not always available when UMKM need. In comparison with using the application of safety stock method (safety stock) more efficient, which is useful as a supplemental supply to protect the production process in the event of a shortage of raw materials due to the delay or uncertainty of the arrival of raw materials. Keywords: Inventory, source of raw materials, raw material prices, EOQ, Safety Stock